2018
DOI: 10.1038/s41598-018-20049-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feature-based attention on flanker interference processing: An fMRI-constrained source analysis

Abstract: The present study examined whether feature-based cueing affects early or late stages of flanker conflict processing using EEG and fMRI. Feature cues either directed participants’ attention to the upcoming colour of the target or were neutral. Validity-specific modulations during interference processing were investigated using the N200 event-related potential (ERP) component and BOLD signal differences. Additionally, both data sets were integrated using an fMRI-constrained source analysis. Finally, the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 97 publications
1
18
0
Order By: Relevance
“…Hence, in these tasks we also analyzed the Gratton effect, which states that congruency effects may be larger after congruent trials than after incongruent trials. Hypothetically, this is because conflict monitoring has been activated during incongruent trials, diminishing possible congruency effects during the following trial (see also Kerns, 2006; Siemann, Herrmann & Galashan, 2018 with regard to serial congruency effects in the Simon and Flanker tasks, respectively).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, in these tasks we also analyzed the Gratton effect, which states that congruency effects may be larger after congruent trials than after incongruent trials. Hypothetically, this is because conflict monitoring has been activated during incongruent trials, diminishing possible congruency effects during the following trial (see also Kerns, 2006; Siemann, Herrmann & Galashan, 2018 with regard to serial congruency effects in the Simon and Flanker tasks, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…In the Simon and Flanker tasks, we also examined how congruency of the previous trial affects the congruency effect on the next trial. Earlier studies have found that for both tasks, the congruency effect is lower after incongruent trials than after congruent trials (Botvinick et al, 2001;Kerns, 2006;Siemann et al, 2018). This is called the Gratton effect and is assumed to reflect conflict monitoring.…”
Section: Trial-level Analysis Of the Executive Cost Effects Learningmentioning
confidence: 95%
“…After meta-analyses of the dual-pathway theory of auditory tasks (Alho et al, 2014;Arnott et al, 2004), additional inferior parietal lobe activity is predicted for spatial stimuli; and middle STG activity, for nonspatial stimuli. Conflict resolution contrasts are predicted to show frontoparietal activation including ACC, IFG, and parietal lobe, as found by Roberts and Hall (2008) and Siemann et al (2018). However, it is unclear whether larger supramodal or auditory-specific networks will be engaged for the spatial (e.g., frontal cortex) and nonspatial (e.g., amodal: MTG; supramodal: cuneus and lingual gyrus) auditory stimuli.…”
Section: Introductionmentioning
confidence: 83%
“…However, the pathways activated by auditory spatial and nonspatial conflict resolution tasks have not been investigated. Siemann, Herrmann, and Galashan (2018) investigated this question with visual stimuli and found comparable networks were activated for visual spatial and nonspatial conflict resolution (dorsal frontoparietal networks in the left MFG, superior parietal lobule, and FEFs), with additional ventral areas recruited specifically for nonspatial conflict resolution (left MTG, cuneus, and lingual gyrus).…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of 435 musicians with absolute pitch, the majority of listeners process pure tones on a continuous scale; 436 the typical listener is unable to categorize a frequency of 261.6 Hz as middle C, and would 437 instead label the tone with an abstract label. This has been shown using another version of an 438 auditory Stroop task where conflict resolution was assessed by congruent and incongruent trials 439 of the stimuli's tone and sung tone name (Schulze, Mueller, & Koelsch, 2013). Unlike musicians 440 without absolute pitch, those with absolute pitch showed activation in the left superior temporal 441 gyrus/sulcus.…”
Section: Comparisons 400mentioning
confidence: 88%